Utilización de variables morfométricas para explicar el comportamiento del peso fresco y eviscerado en tres especies de peces del género Opisthonema (Pisces: Clupeidae) (ING) - Víquez, R. (1992)
An analisys of variance was used to choose the statical model that best explained the fresh and eviscerated weight on the basis of the most important morphometric variables. The analysis showed a significative difference between sexes and between species. Two “proxy” variables were created one variable was related to size and the other to the shape of the sardine, in order to avoid the multicolinearity showed by a correlation analysis. The statistical model obtained is showed in table 10.